(untitled) (Scientia Agropecuaria, 2020)
The genus Staphylococcus comprises many species which can be isolated from many sources and could display plant growth-promoting properties. Moreover, Capsicum species are important export crops in Peru, which have gained greater interest in recent years. Therefore, the objective of this research was to identify Staphylococcus isolates from rhizospheric soil samples of C. annuum cv. Piquillo in La Libertad, Peru. Bacterial isolates were identified by genomic analysis targeting the 16s rRNA gene. Bacteria were isolated from samples by serial dilutions and cultured in solid medium agar plates. Then, genomic DNA extraction from pure and morphologically distinct isolates, 16s rRNA gene amplification, sequencing and bioinformatic analysis were performed. We found four bacterial isolates from the genus Staphylococcus not previously reported in C. annuum rhizospheric soils: Isolate Ca2 and Ca5 which both match to Staphylococcus sp., isolate Ca6 to Staphylococcus arlettae and isolate Ca7 to Staphylococcus xylosus. Further studies to assess these isolates’ impact on crops as well as their potential applications in other fields of research such as antimicrobial development, food processing and pesticide biodegradation are recommended.